The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.12693/aphyspola.116.36
|View full text |Cite
|
Sign up to set email alerts
|

Anharmonicity Effects in Nanocrystals Studied by Raman Scattering Spectroscopy

Abstract: Phonon-phonon interactions were investigated in various nanocrystalline powders like anatase TiO 2−δ , pure CeO 2−δ and ceria doped with Nd(Gd) analyzing temperature dependent Raman spectra of these systems. Phonon confinement model based on size, inhomogeneous strain and anharmonic effects was used to properly describe the evident changes present in the Raman spectra of pure and doped ceria nanocrystalline samples. In small particles of pure and doped ceria nanocrystals, when size effects have minor impact on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
19
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 26 publications
(37 reference statements)
3
19
1
Order By: Relevance
“…It is well known that the variations/shifts in the normal modes with temperature at constant pressure arise either from pure volume contribution, i.e from thermal expansion, or from pure‐temperature contribution, i.e. from cubic and quartic anharmonicities, also known as self‐energy shift, i.e. ω(),T=ω0+ωlatt+ωitalicanitalich …”
Section: Temperature‐dependent Ramanmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that the variations/shifts in the normal modes with temperature at constant pressure arise either from pure volume contribution, i.e from thermal expansion, or from pure‐temperature contribution, i.e. from cubic and quartic anharmonicities, also known as self‐energy shift, i.e. ω(),T=ω0+ωlatt+ωitalicanitalich …”
Section: Temperature‐dependent Ramanmentioning
confidence: 99%
“…It has also been reported that owing to the nanosized particles, the core and shell of the sample may have varying symmetries . It has also been reported that the anharmonic constants related to the peak widths and peak positions are higher in nanocrystals than in the bulk, implying a greater degree of anharmonicity in nanocrystals . Very few experiments have been carried out to investigate the temperature dependence of Raman mode positions and line widths in nanocrystals …”
Section: Introductionmentioning
confidence: 99%
“…This shift of frequency with temperature has contribution from the thermal expansion of the lattice and anharmonic phonon-phonon interaction. The phonon frequency shift as a function of temperature can be expressed as, 34,35 xðTÞ ¼ x 0 þ ðDxÞ latt þ ðDxÞ anh ;…”
Section: Temperature Dependent Behaviormentioning
confidence: 99%
“…The amount of water content is significantly higher in case of NCE18 O and NCG18 O compared to the respective bulk samples.Figure 2 A. F2g Raman mode position for Ce 16 O2 with 81 nm (red solid line) and Ce 18 O2 with 81 nm (blue solid line) obtained at ambient temperature with an incident wavelength of λ = 473 nm. from temperature-induced volume expansion and anharmonicity effects are thus minimized 52,53. 2Bas a function of temperature for CeO2 with 81 nm (red line) and nano-CeO2 with 9 nm grain size (blue line).…”
mentioning
confidence: 99%